2009
DOI: 10.1098/rspa.2009.0502
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate empirical mode decomposition

Abstract: Despite empirical mode decomposition (EMD) becoming a de facto standard for time-frequency analysis of nonlinear and non-stationary signals, its multivariate extensions are only emerging; yet, they are a prerequisite for direct multichannel data analysis. An important step in this direction is the computation of the local mean, as the concept of local extrema is not well defined for multivariate signals. To this end, we propose to use real-valued projections along multiple directions on hyperspheres (n-spheres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
652
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 796 publications
(703 citation statements)
references
References 17 publications
3
652
0
3
Order By: Relevance
“…To obtain monocomponent bases common for all the data channels within multivariate signals in a data-adaptive manner, a generalized multivariate extension of EMD (MEMD) has been developed recently [16], which operate directly on multivariate signals, containing any number of data channels. The operation of the MEMD algorithm rests on the estimation of the local mean of multivariate signals, a key step in EMD-based algorithms which is achieved in single-channel EMD by taking the average of the upper and lower envelopes of the signal in hand, obtained by interpolating the local maxima (upper envelope) and the local minima (lower envelope).…”
Section: Multivariate Empirical Mode Decompositionmentioning
confidence: 99%
“…To obtain monocomponent bases common for all the data channels within multivariate signals in a data-adaptive manner, a generalized multivariate extension of EMD (MEMD) has been developed recently [16], which operate directly on multivariate signals, containing any number of data channels. The operation of the MEMD algorithm rests on the estimation of the local mean of multivariate signals, a key step in EMD-based algorithms which is achieved in single-channel EMD by taking the average of the upper and lower envelopes of the signal in hand, obtained by interpolating the local maxima (upper envelope) and the local minima (lower envelope).…”
Section: Multivariate Empirical Mode Decompositionmentioning
confidence: 99%
“…The multivariate EMD (mEMD) is more generalized extension of EMD suitable for dealing with direct processing of multivariate data for real world applications [30]. Standard EMD revealed that IMFs tend to mimic a filter bank-like decomposition, similar to wavelet decompositions.…”
Section: Multivariate Emd (Memd)mentioning
confidence: 99%
“…This step is complex to perform due to the lack of formal definition of maxima and minima in n-dimensional domains in general EMD. The sampling based on low discrepancy Hammersley sequence is used to generate projections of input signal in [30]. Once the projections along different directions in multidimensional spaces are obtained, their extrema are interpolated via cubic spline interpolation to obtain multiple signal envelopes.…”
Section: Multivariate Emd (Memd)mentioning
confidence: 99%
“…Empirical mode decomposition (Huang et al, 1998) separates fast and slow oscillatory components of non-linear and non-stationary signals into intrinsic mode functions (IMFs), unlike harmonic analysis, which decomposes signals into components that are integer multiples of the fundamental frequency. To align the oscillatory components of ENSO and influenza time series and reduce mode mixing, noise assisted multivariate empirical mode decomposition (Rehman and Mandic, 2010a) which applies multivariate empirical mode decomposition algorithm (Rehman and Mandic, 2010a), was used. The algorithm of multivariate EMD (Rehman and Mandic, 2010a) is as follows:…”
Section: Oscillatory Components Of Enso and Influenza Time Seriesmentioning
confidence: 99%
“…To align the oscillatory components of ENSO and influenza time series and reduce mode mixing, noise assisted multivariate empirical mode decomposition (Rehman and Mandic, 2010a) which applies multivariate empirical mode decomposition algorithm (Rehman and Mandic, 2010a), was used. The algorithm of multivariate EMD (Rehman and Mandic, 2010a) is as follows:…”
Section: Oscillatory Components Of Enso and Influenza Time Seriesmentioning
confidence: 99%